Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian Makanan Pendamping ASI (MP -ASI) Pada Anak Usia 6 - 24 Bulan di Puskesmas Laubaleng Kabupaten Karo Tahun 2023 - Kristina Natalia Simanjuntak; Basaria Manurung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Providing Complementary Food with Breast Milk (MP-ASI) to babies must pay attention to the recommended Nutritional Adequacy Rate (AKG) based on age group and food texture that is appropriate to the development of the toddler's age. This research aims to determine the relationship between maternal knowledge and attitudes and the provision of complementary foods for breast milk (Mp-Asi) in children aged 6 - 24 months at the Laubaleng Community Health Center, Karo Regency in 2023. This type of research is research using an analytical survey with a cross sectional method approach. The population is all mothers who have children aged 6 - 24 months, totaling 46 people. The number of samples used was 46 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 46 respondents, there was a relationship between maternal knowledge and the provision of complementary foods for breast milk (MP-ASI) in children aged 6 - 24 months, showing that the p value = 0.023 < 0.05. It is recommended for Health Workers to increase education regarding Complementary Feeding for Breast Milk (MP-ASI).